2020
DOI: 10.1038/s41598-020-69624-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of acetyl-CoA carboxylase by spirotetramat causes growth arrest and lipid depletion in nematodes

Abstract: Plant-parasitic nematodes pose a significant threat to agriculture causing annual yield losses worth more than 100 billion US$. Nematode control often involves the use of nematicides, but many of them including non-selective fumigants have been phased out, particularly due to ecotoxicological concerns. Thus new control strategies are urgently needed. Spirotetramat (SPT) is used as phloem-mobile systemic insecticide targeting acetyl-CoA carboxylase (ACC) of pest insects and mites upon foliar application. Howeve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Similarly, many studies showed that several environmental toxicants such as nanoparticles decreased lifespan of C. elegans 43,44 . Furthermore, pesticides including paichongding and spirotramat interrupted life cycle and shortened lifespan of nematodes 45,46 . These findings implied that exposure to environmental xenobiotics such as fluopimomide adversely affected survival of C. elegans .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, many studies showed that several environmental toxicants such as nanoparticles decreased lifespan of C. elegans 43,44 . Furthermore, pesticides including paichongding and spirotramat interrupted life cycle and shortened lifespan of nematodes 45,46 . These findings implied that exposure to environmental xenobiotics such as fluopimomide adversely affected survival of C. elegans .…”
Section: Resultsmentioning
confidence: 91%
“…43,44 Furthermore, pesticides including paichongding and spirotramat interrupted life cycle and shortened lifespan of nematodes. 45,46 These findings implied that exposure to environmental xenobiotics such as fluopimomide adversely affected survival of C. elegans. An increase in ROS accumulation indicated that the nematodes were under oxidative stress, which was considered to be an important factor leading to aging.…”
Section: Exposure To Fluopimomide At Sublethal Doses Shortened Lifesp...mentioning
confidence: 97%
“…28,29 Spirotetramat degrades readily in soil, 59 and moderate application protects plants without affecting their growth. 60 It also effectively controls pests such as Psyllidae, Aleyrodidae, Coccoidea, Lygus lucorum, Caenorhabditis elegans, 29 and Frankliniella occidentalis 61 and has long-lasting efficacy, providing control for up to 8 weeks.…”
Section: ■ Insecticidal Activitymentioning
confidence: 99%
“…The most commonly used presently are spirodiclofen, spirotetramat, and spiromesifen (developed by Bayer), which target acetyl-CoA carboxylase (ACC) in pests, by inhibiting lipid synthesis, resulting in efficient, rapid insecticidal activity (Figure ). As a result, global sales of these three insecticides have risen since their launch. Spirodiclofen sales have soared since it was first listed in 2003.…”
Section: Insecticidal Activitymentioning
confidence: 99%
See 1 more Smart Citation